KONSENTRASI ZPT AUKSIN DAN LAMA PERENDAMAN TERHADAP PERTUMBUHAN BIBIT PORANG (Amorphophallus onchophyllus Prain.) - Juliarti, Anna; Prastyaningsih, Sri Rahayu; Utami, Sri (Agrienvi: Jurnal Ilmu Pertanian, 2023)
Porang is in great demand because it is very prospective and expensive. Bulbil Porang's bulbil dormancy period depends on the season. ZPT (Growth Regulatory Substance) is very important as a trigger for breaking dormancy and stimulating roots. The aim of this study was to analyze the growth response of Porang shoots to the concentration of ZPT Auxin and the immersion time. Research design applied was Factorial RAL with 2 factors, namely Auxin concentration and Porang bulbil immersion time. Auxin concentration consisted of 4 levels, namely control (without Auxin), 100 mg/l water, 300 mg/l water, and 500 mg/l water. The immersion time factor consists of 3 levels, namely control (immersed); 1.5 hours of immersion, and 3 hours of immersion. The results showed that the 1.5 hour auxin ZPT immersion time had a significant effect on all observation parameters, namely shoot time, number of shoots, height and diameter of Porang shoots. The best growth percentage of Porang shoots resulted from the A1L1 interaction (auxin 100 mg/l water: 1.5 hour immersion). The interaction between A2L1 (300 mg/l water auxin: 1.5 hours immersion) and A3L1 (300 mg/l water: 1.5 hours immersion) treatment resulted in the best increase in height and diameter of Porang shoots.